Fourteen years of quality improvement education in healthcare: a utilisation-focused evaluation using concept mapping. Issue 4 (13th December 2019) - Smith, Frida; Alexandersson, Patrik; Bergman, Bo; Vaughn, Lisa; Hellström, Andreas
Abstract : Background: The need for training in quality improvement for healthcare staff is well acknowledged, but long-term outcomes of such training are hard to evaluate. Behaviour change, improved organisational performance and results are sought for, but these variables are complex, multifactorial and difficult to assess. Aim: The purpose of this article is to explore the personal and organisational outcomes identified by participants over 14 years of university-led QI courses for healthcare professionals. Method: Inspired by the Kirkpatrick model for evaluation, we used concept mapping, a structured mixed method that allows for richness of data to be captured and visualised by inviting stakeholders throughout the process. In total, 331 previous course participants were included in the study by responding to two prompts, and 19 stakeholders taking part in the analysis process by doing the sorting. Result: Two maps, one for personal outcomes and one for organisational outcomes, show clusters of the responses from previous course participants and how the outcomes relate to each other in meta-clusters. Both maps show possible long-term outcomes described by the previous course participants. Conclusion: The results of this study indicate that it is possible that training in quality improvement with a strong experiential pedagogical approach fosters a long-term improvement capability for the course participants and, even more important, a long-term improvement capability (and increased improvement skill) in their respective organisations.